Ritualism as a reflection of social transformation and the researcher's (lack of) power - Klobčar, Marija (Traditiones (Ljubljana), 2012)
This paper describes various views of the Kamnik folklore event Traditional Costume and Clothing Heritage Days in order to illuminate the relationship researchers have with these cultural phenomena. It analyzes the origins of the Kamnik event, revealing its social significance, and also analyzes the reasons that this event has attained ritual status for some. Although the event still plays this role today for some people, it has gradually also gained completely different meanings. The researcher is present as an observer, but also as an advisor when asked by the organizers, at which point he is faced with numerous issues connected with the concept of authenticity. This article therefore places the researcher's role within the context of views that problematize his a priori position and call attention to the fact that the researcher should participate at the level of informer. Considering the varied meanings this event has for individuals, and considering their diverse relations to folklorism, which are recognized in both the organizers and the participants, the question is which of these views ought to be taken into account.
Keywords: ethnology; Etnologija; Folklorne prireditve; costumes; Noša; Kamnik; folklorne skupine; narodne noše